2014
DOI: 10.1177/1098214014545828
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Assessing the Performance of Nonprofit Organizations

Abstract: Performance measurement has gained increased importance in the nonprofit sector, and contemporary literature is populated with numerous performance measurement frameworks. In this article, we seek to accomplish two goals. First, we review contemporary models of nonprofit performance measurement to develop an integrated framework in order to identify directions for advancing the study of performance measurement. Our analysis of this literature illuminates seven focal perspectives on nonprofit performance, each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 91 publications
(142 reference statements)
1
98
0
5
Order By: Relevance
“…A recent study by Lee and Nowell (2015), identified various perspectives that can be adopted in measuring and conceptualizing performance of the NPO. The perspectives are inputs, organizational capacity, outputs, outcomes, public value accomplishment and network/institutional legitimacy.…”
Section: Non-financial Measurementmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study by Lee and Nowell (2015), identified various perspectives that can be adopted in measuring and conceptualizing performance of the NPO. The perspectives are inputs, organizational capacity, outputs, outcomes, public value accomplishment and network/institutional legitimacy.…”
Section: Non-financial Measurementmentioning
confidence: 99%
“…Examples of performance measurement for this approach as summarized by Lee and Nowell (2015) are increase in revenue, diversity in revenue stream, ability to acquire and manage human resources, employee satisfaction, motivation, retention. Additional measurements as suggested by Sillanpää (2011) are utilization of facilities and financial resources sufficiency.…”
Section: Inputmentioning
confidence: 99%
See 3 more Smart Citations